The effect of a community based pulmonary rehabilitation programme on the quality of life of patients with pulmonary tuberculosis - De Grass, Donna (Division of Physiotherapy, 2014)
The purpose of this study is to determine whether a community based rehabilitation exercise programme had an effect on pulmonary function, exercise tolerance and Health Related Quality of Life (HRQoL) in patients diagnosed with Pulmonary Tuberculosis (PTB). The prevalence of PTB in South Africa is one of the highest in the African continent. Assessing the effectiveness of the programme could provide further methods in improving compliance to pharmaceutical medication as well as an improvement in the morbidity experienced after diagnosis of PTB.